1987
DOI: 10.1088/0031-8949/36/4/005
|View full text |Cite
|
Sign up to set email alerts
|

Revised analysis of singly ionized xenon, Xe II

Abstract: We present a revised analysis of the spectrum of singly ionized xenon, Xe II. This spectrum has been reanalyzed on the basis of the wavelength material published by Drs J. C. Boyce and C. J. Humphreys. The latter has kindly placed the original wavelength list covering the wavelength range 10 220-390 Å at our disposal. We report 161 energy levels which have been identified on the basis of classifications of 950 lines. We report the first f and g levels in Xe II. Also a number of g-factors have been determined f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
147
0
1

Year Published

1988
1988
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(164 citation statements)
references
References 53 publications
16
147
0
1
Order By: Relevance
“…This line, as well as all the other lines with Δλ ∼ −0.1 Å has a 6d or a 7s level as upper level. The uncertainty of the energy of these levels is on the order of 0.5 cm −1 according to Hansen & Persson (1987). Figures 1-4 show the comparison of the HR 6000 astrophysical log g f -values for Xe ii with the log g f -values taken from the NIST database and log g f -values derived from the spectra of HD 71066, 46 Aql, and HD 175640, respectively (Table B.1, Col. 5).…”
Section: Stellar Wavelengths and The Astrophysical Log Gf -Values Formentioning
confidence: 99%
See 1 more Smart Citation
“…This line, as well as all the other lines with Δλ ∼ −0.1 Å has a 6d or a 7s level as upper level. The uncertainty of the energy of these levels is on the order of 0.5 cm −1 according to Hansen & Persson (1987). Figures 1-4 show the comparison of the HR 6000 astrophysical log g f -values for Xe ii with the log g f -values taken from the NIST database and log g f -values derived from the spectra of HD 71066, 46 Aql, and HD 175640, respectively (Table B.1, Col. 5).…”
Section: Stellar Wavelengths and The Astrophysical Log Gf -Values Formentioning
confidence: 99%
“…This energy difference corresponds to a difference of 0.1 Å in wavelengths. Saloman (2004), who performed a critical compilation of all the work on energy levels and wavelengths of Xe ii made up to that time, adopted the data from Hansen & Persson (1987) for almost all the lines of the optical region. The Saloman (2004) critical compilation is the one adopted by the NIST database.…”
Section: Introductionmentioning
confidence: 99%
“…Fahlman et al (59,60) have also reported Xe 5 s PES spectra at quite good energy resolution, and also obtained angular distribution information over the photon-energy range 28.5-74. intensities. Figure 6 shows a theoretical spectrum obtained using the intensities as calculated by Hansen and Persson using CI methods (27,45) and convoluted with the experimental energy resolution (0.34 eV). Unlike the case of the Ar 3s CI calculations (30), the xenon calculations (27,45) included a wide range of final ion states and not just those of the principal series (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 6 shows a theoretical spectrum obtained using the intensities as calculated by Hansen and Persson using CI methods (27,45) and convoluted with the experimental energy resolution (0.34 eV). Unlike the case of the Ar 3s CI calculations (30), the xenon calculations (27,45) included a wide range of final ion states and not just those of the principal series (i.e. not just those of ~S~~~~( ' D )~S (~S symmetry).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation